Impact of biochar and lignite‐based amendments on microbial communities and greenhouse gas emissions from agricultural soil - Changjian Li; Yunwu Xiong; Jiaye Zou; Li Dong; Ping Ren; Guanhua Huang (Vadose Zone Journal, 2021)
Abstract Understanding the responses of the microbial community and greenhouse gas (GHG) emissions to the incorporation of different organic amendments is essential for their proper utilization. In this study, laboratory‐incubated microcosm experiments were conducted to investigate the short‐term effects of pine‐wood biochar and lignite‐based amendment on the microbial communities and GHG emissions from agricultural soil. Soils amended at five different application rates were incubated for 19 d under the conditions of 60% water‐filled pore space and 25 °C. Microbial biomass in the amended soil after incubation was measured by the solid colony counting method, and the soil microbial diversity was assayed using a Biolog EcoPlate. The biochar and lignite‐based amendment had distinct effects on the soil microbial communities and GHG emissions. The microbial community growth and utilization of C sources were improved by the biochar but restrained by the lignite‐based amendment in most cases. The biochar and lignite‐based amendment had a minor impact on methane emissions. Carbon dioxide emissions were promoted by the biochar and inhibited by the lignite‐based amendment during the short‐term incubation period. Nitrous oxide emissions decreased with the application rate of biochar but increased with the rate of lignite‐based amendment. The addition of biochar at a rate of 3–4% and lignite‐based amendment at a rate of <1% has the potential to improve soil quality. Salt leaching is required to avoid accumulation when the biochar and lignite‐based amendments are applied. The findings can provide a reference for the application of biochar and lignite‐based amendment in silt loam soil.